Management of pouch‐vaginal fistulas – experience from our institution. (5th December 2019) - Sivathondan, P. C.; Bloemendaal, A.; Travis, S.; Mortensen, N.; George, B. D.
Abstract: Aim: Pouch–vaginal fistula (PVF) is an uncommon but serious complication of ileo‐anal pouch reconstruction. This study aimed to review the recent management of PVF, in particular the role of anti‐tumour necrosis factor (anti‐TNF) drugs. Method: All patients presenting for management of PVF to our surgical service between 2007 and 2016 were studied. The median duration of follow‐up from diagnosis of PVF was 6 years. Details of the original pouch surgery, timing of presentation of PVF, management and final outcome were recorded. Primary outcome was gastrointestinal (GI) continuity (as defined by the presence or absence of a stoma). Results: A total of 23 patients were identified (median age 45 years) of whom nine had pelvic sepsis at the time of original pouch surgery. Management included local surgical repair, defunctioning ileostomy, pouch excision and anti‐TNF therapy. GI continuity was achieved in 12 patients (52%). Healing of the PVF was achieved in 12 patients (52%). Pelvic sepsis was significantly associated with the need for a long‐term ileostomy ( P  = 0.009). Biological therapy was used in 12 patients, of whom seven maintained GI continuity. Patients with late presentation PVF (60 months or longer postsurgery) and those with clinical features of Crohn's disease appeared to benefit from anti‐TNF treatment. Conclusion: PVF remains a challenging problem with overall healing rates and GI continuity rates of just over 50%. Anti‐TNF therapy may have a role in patients with late presentation PVF and those with features suggestive of Crohn's disease.